Operative Versus Nonoperative Treatment of Acute Achilles Tendon Rupture: A Propensity Score–Matched Analysis of a Large National Dataset. Issue 2 (24th February 2023) - Crook, Bryan S.; Varshneya, Kunal; Meyer, Lucy E.; Anastasio, Albert; Cullen, Mark M.; Lau, Brian C.
Background: No consensus exists regarding the superiority of operative versus nonoperative management for Achilles tendon ruptures, as multiple randomized controlled trials conducted since the advent of early mobilization protocols have found outcomes for these 2 interventions to be more similar than were previously held. Purpose: To use a large national database to (1) compare reoperation and complication rates between operative and nonoperative treatment of acute Achilles tendon ruptures and (2) evaluate trends in treatment and cost over time. Study Design: Cohort study; Level of evidence, 3. Methods: The MarketScan Commercial Claims and Encounters database was used to identify an unmatched cohort of 31, 515 patients who sustained primary Achilles tendon ruptures between 2007 and 2015. Patients were stratified into operative and nonoperative treatment groups, and a propensity score—a matching algorithm—was used to establish a matched cohort of 17, 996 patients (n = 8993 per treatment group). Reoperation rates, complications, and aggregate treatment costs were compared between groups with an alpha level of .05. A number needed to harm (NNH) was calculated from the absolute risk difference in complications between cohorts. Results: The operative cohort experienced a significantly larger total number of complications within 30 days of injury (1026 vs 917; P = .0088). The absolute increase in cumulative risk was 1.2% with operative treatment, which resulted in an NNH of 83. Neither 1-year (1.1% [operative] vs 1.3% [nonoperative]; P = .1201) nor 2-year reoperation rates (1.9% [operative] vs 2% [nonoperative]; P = .2810) were significantly different. Operative care was more expensive than nonoperative care at 9 months and 2 years after injury; however, there was no difference in cost between treatments at 5 years. Before matching, the rate of surgical repair for Achilles tendon rupture remained stable, from 69.7% to 71.7% between 2007 and 2015, indicating little change in practice in the United States. Conclusion: Results indicated no differences in reoperation rates between operative and nonoperative management of Achilles tendon ruptures. Operative management was associated with an increased risk of complications and higher initial costs, which dissipated over time. Between 2007 and 2015 the proportion of Achilles tendon ruptures managed operatively remained similar despite increasing evidence that nonoperative management of Achilles tendon rupture may provide equivalent outcomes.